PERCEPTION AND AWARENESS ABOUT BIRTH INTERVAL IN A SAMPLE OF WOMEN ATTENDING OUTPATIENT CLINICS OF TEACHING HOSPITALS IN ERBIL CITY - Rasul, Aziza Sdiq; Al-Hadithi, Tariq (Journal of Sulaimani Medical College, 2014)
Background and Objectives Adequate child-spacing is considered a positive factor for the health of mothers and their children. This study was done to assess perceptions of women about birth spacing and associated socio-demographic factors. Methods A cross-sectional study was done from April 2010 through April 2011 on 500 mothers aged 15–52 years attending outpatient clinics of teaching hospitals in Erbil city. All had given birth to at least 2 children within the last 10 years prior to the study. Data was collected using a questionnaire including socio-demographic information and perception about birth spacing. Results Only 25.6% preferred a birth interval of < 3 years, while the rest favored ≥ 3 years. Adequate birth spacing preference was significantly associated with younger age at marriage. Nearly half were not aware of the mortality and morbidity risks associated with short interval. Conclusion Women’s perception and awareness in Erbil city about birth interval is comparable to that of neighbouring countries. Nearly half of the women lacked awareness of importance of adequate birth spacing.
Keywords: Birth spacing; Perception and awareness; Iraq